HIV-1 replication and latency are balanced by mTOR-driven cell metabolism - Crater, Jacqueline M.; Nixon, Douglas F.; Furler O’Brien, Robert L. (Frontiers in Cellular and Infection Microbiology, 2022)
Human Immunodeficiency virus type 1 (HIV 1) relies on host cell metabolism for all aspects of viral replication. Efficient HIV 1 entry, reverse transcription, and integration occurs in activated T cells because HIV 1 proteins co opt host metabolic pathways to fuel the anabolic requirements of virion production. The HIV 1 viral life cycle is especially dependent on mTOR, which drives signaling and metabolic pathways required for viral entry, replication, and latency. As a central regulator of host cell metabolism, mTOR and its downstream effectors help to regulate the expression of enzymes within the glycolytic and pentose phosphate pathways along with other metabolic pathways regulating amino acid uptake, lipid metabolism, and autophagy. In HIV 1 pathogenesis, mTOR, in addition to HIF 1α and Myc signaling pathways, alter host cell metabolism to create an optimal environment for viral replication. Increased glycolysis and pentose phosphate pathway activity are required in the early stages of the viral life cycle, such as providing sufficient dNTPs for reverse transcription. In later stages, fatty acid synthesis is required for creating cholesterol and membrane lipids required for viral budding. Epigenetics of the provirus fueled by metabolism and mTOR signaling likewise controls active and latent infection. Acetyl CoA and methyl group abundance, supplied by the TCA cycle and amino acid uptake respectively, may regulate latent infection and reactivation [1]. Thus, understanding and exploring new connections between cellular metabolism and HIV 1 pathogenesis may yield new insights into the latent viral reservoirs and fuel novel treatments and cure strategies.